Developing Leadership in Managers to Facilitate the Implementation of National Guideline Recommendations: A Process Evaluation of Feasibility and Usefulness - Malin Tistad; Susanne Palmcrantz; Lars Wallin; Anna Ehrenberg; Christina B. Olsson; Göran Tomson; Lotta Widén Holmqvist; Wendy Gifford; Ann Catrine Eldh (Kerman University of Medical Sciences, 2016)
Background: Previous research supports the claim that managers are vital players in the implementation of clinical practice guidelines (CPGs), yet little is known about interventions aiming to develop managers' leadership in facilitating implementation. In this pilot study, process evaluation was employed to study the feasibility and usefulness of a leadership intervention by exploring the intervention's potential to support managers in the implementation of national guideline recommendations for stroke care in outpatient rehabilitation. Methods: Eleven senior and frontline managers from five outpatient stroke rehabilitation centers participated in a fourmonth leadership intervention that included workshops, seminars, and teleconferences. The focus was on developing knowledge and skills to enhance the implementation of CPG recommendations, with a particular focus on leadership behaviors. Each dyad of managers was assigned to develop a leadership plan with specific goals and leadership behaviors for implementing three rehabilitation recommendations. Feasibility and usefulness were explored through observations and interviews with the managers and staff members prior to the intervention, and then one month and one year after the intervention. Results: Managers considered the intervention beneficial, particularly the participation of both senior and frontline managers and the focus on leadership knowledge and skills for implementing CPG recommendations. All the managers developed a leadership plan, but only two units identified goals specific to implementing the three stroke rehabilitation recommendations. Of these, only one identified leadership behaviors that support implementation. Conclusion: Managers found that the intervention was delivered in a feasible way and appreciated the focus on leadership to facilitate implementation. However, the intervention appeared to have limited impact on managers' behaviors or clinical practice at the units. Future interventions directed towards managers should have a stronger focus on developing leadership skills and behaviors to tailor implementation plans and support implementation of CPG recommendations.